TRADISI PEMAHAMAN HADIS DALAM KITAB GARIB AL-HADIS DAN TRANSFORMASINYA KE TRADISI KITAB SYARAH HADIS - Suryadilaga, Alfatih (Nabawi: Journal of Hadith Studies, 2020)
Sejarah awal Islam keberadaan keilmuan atas pemahaman hadis belum diperlukan karena sosok orang yang memberi penjelas atas al-Qur’an masih hidup. Perkembangan pemahaman hadis seusai kenabian Muhammad Saw. melahirkan pemahaman hadis yang sangat variatif dan melahirkan banyak kitab-kitab hadis yang terhimpun dalam keilmuan gharib al-hadith. Penelitian ini termasuk penelitian kualitatif dengan metode interpretif konseptual serta menggunakan pendekatan historis atas beberapa kitab tentang gharib al-hadith dan sharh al-hadith. Artikel ini menjelaskan pemahaman hadis dalam konteks gharib al-hadith tersebut, bagaimana latar belakang kelahirannya serta menjelaskan tentang transformasi keilmuan tersebut dengan keilmuan syarah hadis. Hasil karya ulama hadis atas keilmuan hadis sangat variatif dengan delapan model kajian dan dimulai dalam bentuk sederhana seperti kamus yang hanya menjelaskan matan hadis yang kurang dimengerti oleh masyarakat. Selain itu, transformasi keilmuan gharib al-hadith ke syarah hadis adalah melahirkan bentuk yang sangat kompleks dalam pemahaman yang menjelaskan aspek menyeluruh hadis yakni sanad dan periwayat hadis serta matan hadis. Walaupun demikian, keberadaan syarah juga mengikuti perkembangan zaman dan kecenderungan penulisnya dengan melahirkan tiga bentuk yaiu syarah singkat, syarah medium dan syarah panjang lebar (lengkap). Ketiga bentuk syarah hadis tersebut telah menjadi transformasi pemahaman hadis di era sebelumnya yakni di masa gharib al-hadith dengan kajian yang terbatas.Kata Kunci: Pemahaman Hadis, Gharib al-Hadith, Sharh al-Hadith.AbstractEarly history of Islam the existence of science for understanding the hadith is not needed because the figure of the person who gives an explanation of the Qur'an is still alive. The development of the understanding of the hadith after the prophethood of Muhammad. gave birth to a very varied understanding of hadith and gave birth to many books of hadith that are collected in the science of garib al-hadith. This research includes qualitative research with conceptual interpretive methods and uses a historical approach to several books about gharib al-hadith and sharh al-hadith. This article explains the understanding of the hadith in the context of the garib al-hadith, how the background of its birth and explains the transformation of the science with the knowledge of the tradition of hadith. The results of the hadith scholar's work on the science of hadith are very varied with eight models of study and begin in a simple form like a dictionary which only explains the tradition of tradition which is less understood by the public. In addition, the transformation of scientific knowledge garib al-hadith into the tradition of shari'a is giving birth to a very complex form of understanding that explains the overall aspects of the hadith namely sanad and narrators of traditions and traditions of traditions. Nevertheless, the existence of sharia also follows the development of the times and the tendency of the author to give birth to three forms of short syarah, medium syarah and long syarah (complete). The three forms of hadith shari'ah have been transformed into the understanding of hadith in the previous era, namely in the period of garib al-hadith with limited studies.Keywords: Understanding of  Hadith, Gharib al-Hadith, Sharh al-Hadith.